2005
DOI: 10.7326/0003-4819-142-9-200505030-00013
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Exercise Therapy for Nonspecific Low Back Pain

Abstract: Background: Exercise therapy is widely used as an intervention in low back pain.Objective: To evaluate the effectiveness of exercise therapy in adult nonspecific acute, subacute, and chronic low back pain versus no treatment and other conservative treatments.Data Sources: MEDLINE, EMBASE, PsychInfo, CINAHL, and Cochrane Library databases to October 2004; citation searches and bibliographic reviews of previous systematic reviews.Study Selection: Randomized, controlled trials evaluating exercise therapy for adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
303
0
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(331 citation statements)
references
References 86 publications
10
303
0
18
Order By: Relevance
“…For individuals with chronic low-back pain, exercise therapy appears to be somewhat effective at improving function. In adults with subacute low back pain there is some evidence that a graded activity programme improves absenteeism outcomes [29]. For workers with prolonged fatigue complaints, it was found that physical training improved physiological parameters and had a positive effect on fatigue complaints [30].…”
Section: Exercise Therapy and Graded Activitymentioning
confidence: 99%
“…For individuals with chronic low-back pain, exercise therapy appears to be somewhat effective at improving function. In adults with subacute low back pain there is some evidence that a graded activity programme improves absenteeism outcomes [29]. For workers with prolonged fatigue complaints, it was found that physical training improved physiological parameters and had a positive effect on fatigue complaints [30].…”
Section: Exercise Therapy and Graded Activitymentioning
confidence: 99%
“…However, a meta-analysis of exercise therapy trials in patients with chronic LBP has shown that despite statistically significant improvements, the effect size of exercise (mean treatment effect) was small for pain (7 points out of 100) and disability (3 points out of 100) compared with no treatment or other conservative treatments [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Exercise therapy (ET) remains one of the conservative mainstays of treatment for chronic lumbar spine pain, and may be tailored to include aerobic exercise, muscle strengthening, and stretching exercises [49]. Significant variation in regimen, intensity, and frequency of prescribed programs presents challenges to assessing efficacy among patients [50].…”
Section: Exercise-based and Behavioral Interventions Exercise Therapymentioning
confidence: 99%
“…One meta-analysis of the current literature exploring the role of ET in patients with varying duration of symptoms found a graded exercise program implemented within the occupational setting demonstrated some effectiveness in subacute LBP. Among those suffering chronic pain symptoms, small, but statistically significant improvements were observed among patients, with regard to pain reduction and functional improvement [49]. The optimal approach to exercise therapy in chronic low back pain sufferers appears to be those regimens involving an individually-designed exercise program emphasizing stretching and muscle strengthening, administered in a supervised fashion, with high frequency and close adherence.…”
Section: Exercise-based and Behavioral Interventions Exercise Therapymentioning
confidence: 99%